Turkish cinematograph role in terms of nation building (Journal of Oriental Studies, 2016)
Turkish cinematograph role in terms of nation building, his development path, as well as modern cultural policy in this field is investigated in this article. Turkish cinematograph as the most modern, mobile and mass type of art reflects the processes going down  in the society, as well as takes part an active participation in formation of moral values, behavioral stereotypes, cultural and national identities of country citizens. National identity is expressed not only in the films of historical plan, but also in the films of modernity and future, such as  ethno-cultural traditions of the people are shown in them. The author unfolds the concept “deep nation” and considers the effect of Kemalist ideology to the culture and cinematograph.
Keywords: nation building; cultural policy; cinematograph; identity.